Analisis Komposit Karbon Aktif Dari Tongkol Jagung Dengan Aktivator NaCL Terhadap Hasil Morfologi Dan Sifat Fisik - Lathifah, Hana; Rosidah, Afira Ainur; Yunus, Muhammad (Rekayasa Material, Manufaktur dan Energi, 2025)
Corn cobs (Zea mays L.) can produce charcoal as a source of carbon. Carbon is a potential candidate for reducing exhaust gas emissions containing hydrocarbons, carbon dioxide, and nitrogen dioxide. This research aims to convert corn cobs into activated carbon by adding NaCl activator in concentrations of 0%, 8%, and 16% and then compositing it with sago starch. FTIR testing occurred on the carbon from corn cobs before and after activation to analyze the functional groups in the activated carbon. The carbon was then composited with a ratio of 75:25 and subjected to SEM-EDX testing, moisture content analysis, and ash content analysis. FTIR testing revealed the carbonyl group (C-O) that could reduce emission levels. SEM-EDX testing showed that higher concentrations of NaCl activator (16%) resulted in more and smaller pores. Moisture content analysis indicated that higher concentrations of activators led to increased moisture content. Conversely, ash content analysis showed that lower concentrations of activator resulted in higher ash content. The tests concluded that the optimal composite of activated carbon from corn cobs and sago starch existed at an 8% NaCl activator concentration and a 75:25 composition, making it a promising candidate for reducing exhaust gas emissions.